The prevalence, clinical profi le and surgical outcomes of children presenting with vascular ring and pulmonary sling - Chinawa JM; Agarwal V; Garekar S; Gaikwad S; Trivedi B (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Background: Vascular anomalies are rare abnormalities which present with inspiratory stridor andrecurrent respiratory tract infection. They are the commonest causes of mortality and morbidity in children  due to misdiagnosis. They comprise about less than 4% of congenital heart diseases. The commonest of   these anomalies were vascular ring and pulmonary sling. Objectives: The objective of this study was to determine the prevalence, pattern of presentation andsurgical outcomes of children presenting with vascular ring and pulmonary sling. Methods: A cross-sectional retrospective study in which a review of the records of all children attending Fortis hospital over a 3-year period (2012- and 2015) was undertaken. Data were analyzed using SPSS 20. Frequencies, rates and proportions were represented in tables. Children with confi rmed diagnosis of vascular rings and pulmonary slings are included while other causes of stridor were excluded from this study.